Formulation of a shelf stable, minimally processed cranberry chutney - Mills, McKenna; Savage, Sierra; Alexander, Hannah; Herl, Bethany; Getty, Kelly J.K. (My University, 2017)
Known for their high level of antioxidants, cranberries ranked number one in antioxidant content with 9.584 mmol/100grams, when compared to nineteen other common fruits. For the past few years, consumer trends continue to go towards healthy, minimally processed items with clean labels. The goal of this project was to develop a cranberry chutney consisting of a variety of fruits, peppers, and spices that are minimally processed, contains a clean label, and shelf life similar to a shelf stable canned product. The secondary focus was to use whole cranberries in a new product. The total cranberry content of our chutney was 30%. Other ingredients were 26.3% pear, 13.8% apple, 12.1% canned crushed pineapple, 12.1% sugar, 2.85% Anaheim pepper, 1.1% cilantro, and 1.1% fresh ginger. Only some of the ingredients were pulverized, in order to achieve optimum texture and mouthfeel. The product was minimally processed to an internal temperature of 71.1°C, held for 1 minute, filled above 65.5°C and inverted for 5 min. Once cooled, pH and water activity levels were measured. Two more samples were put into the accelerated shelf life incubator at 40.1℃. After 4 weeks, pH was evaluated. For the 8 week sample, microbial testing was done using 3M plates for aerobic plate count, E. coli/coliforms, and yeast/mold populations. The plates were incubated at 37℃ and checked at day 3 and 5 for colony growth. An accelerated shelf life study proved a one-year shelf life of our canned product. Microbial testing further confirmed this result. For aerobic plate count, E. coli/coliforms, and yeast/molds, the populations were below the detectable limit of <10 CFUs/ml. The pH levels for week 0, 4, and 8 were 2.98, 3.01, and 2.97. Because the chutney contains ingredients that are already naturally acidic, this product is considered a formulated acid food. However, the water activity was high at a level of 0.976. The chutney product was naturally acidic (pH 3.0) and applied a minimally processed heat treatment that was able to achieve an estimated shelf life of 1 year. Once opened, this product must be refrigerated and used within 4 weeks.
Keywords: Spring 2017